2016
DOI: 10.1111/1471-0528.14143
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influenza and birth outcomes: systematic review of comparative studies

Abstract: BackgroundAlthough pregnant women are considered at high risk for severe influenza disease, comparative studies of maternal influenza and birth outcomes have not been comprehensively summarised.ObjectiveTo review comparative studies evaluating maternal influenza disease and birth outcomes.Search strategyWe searched bibliographic databases from inception to December 2014.Selection criteriaStudies of preterm birth, small‐for‐gestational‐age (SGA) birth or fetal death, comparing women with and without clinical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
120
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 90 publications
(288 reference statements)
3
120
2
Order By: Relevance
“…The risks of hospitalisation and complications for respiratory illness during the influenza season are higher for pregnant women and increase by trimester . Furthermore, pregnant women infected with influenza might be more likely to have adverse birth outcomes …”
Section: Introductionmentioning
confidence: 99%
“…The risks of hospitalisation and complications for respiratory illness during the influenza season are higher for pregnant women and increase by trimester . Furthermore, pregnant women infected with influenza might be more likely to have adverse birth outcomes …”
Section: Introductionmentioning
confidence: 99%
“…These efforts have led to recent publications from LMICs, supported by WHO, that provide important influenza disease burden data ( 34 ). WHO has also sponsored reviews of influenza-associated disease burden among pregnant women and their infants ( 35 , 36 ). Additional multinational collaborations are under way that will continue to develop more credible global influenza mortality and hospitalization estimates based on recent work to develop national estimates, as well as information on influenza burden among key high-risk groups (Figure) ( 6 ).…”
Section: Ongoing Work To Address the Gaps And Future Needsmentioning
confidence: 99%
“…Third, Hutcheon et al also concluded that the observed fetal benefits of maternal influenza immunization are biologically implausible, and they supported this claim with a forthcoming (unpublished) systematic review in which minimal support for a strong association between maternal influenza illness and adverse birth outcomes was found (9). We disagree; not only is biological plausibility among the least important of the classic Bradford Hill criteria for assessing causality (17), but the conclusion reached by Hutcheon et al ignores compelling empirical evidence to the contrary.…”
mentioning
confidence: 95%
“…These differences might be particularly pronounced when comparing findings between geographic regions because climate, socioeconomic and nutritional status, and the baseline risk of adverse outcomes may all influence disease epidemiology. For their sample size calculations, Hutcheon et al used published estimates of influenza incidence and preterm birth rates (see Web Table 1 of their article), as well as measures of the association between maternal influenza illness and preterm birth calculated from previous observational studies (9). These estimates were derived almost entirely from studies conducted in temperate climates (predominantly the United States and Canada) with relatively short influenza seasons and low baseline rates of adverse birth outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation